Effect of drying on the physical properties of adzuki bean - Mendes, Udenys Cabral [UNESP]; Resende, Osvaldo; Donadon, Juliana Rodrigues; Almeida, Dieimisson Paulo [UNESP]; Da Rocha, Anisio Correa; De Oliveira, Daniel Emanuel Cabral (Universidade Estadual de Londrina, 2016)
The goal of the present study was to assess the effect of drying on the physical properties of adzuki bean (Vigna angularis Willd.). Adzuki beans with moisture content of 47.9% were dried in a oven with forced air ventilation at temperatures of 40, 60 and 80 °C and relative humidity of 18.5, 8.6, and 3.8%, respectively, until the moisture content reached 12.9%. We used 15 adzuki beans individualised in aluminium capsules. The orthogonal axes of the beans (length, width, and thickness) were measured at intervals of five percentage points during the reduction of moisture content. The parameters determined were: sphericity; circularity; volume of beans; volumetric contraction index; volume contraction percentage; surface area; projected area; and surface-volume ratio. The drying conditions altered the physical properties of adzuki bean. As a result of moisture content reduction, there was increased sphericity and surface-volume ratio, and decreased volume, unitary volumetric contraction, surface area, and projected area. Circularity was not influenced by the drying temperatures within the range of moisture content analysed.
Keywords: Shape; Size; Vigna angularis Willd; Volume